Simultaneous voltammetric determination of acetaminophen and caffeine at a graphite and polyurethane screen-printed composite electrode - Saciloto,Thalita R. (2013)
A selective electrochemical method was developed for the individual or simultaneous determination of acetaminophen and caffeine in phosphate buffer pH 6.0 on graphite and polyurethane screen-printed composite electrode (EIGPU) using Differential Pulse Voltammetry (DPV). The oxidation peaks of acetaminophen and the caffeine appeared at 0.3 V and 1.3 V(vs. pseudo-Ag/AgCl), respectively, showing the possibility of simultaneous determination of both analytes, at the EIGPU, besides the individual determination. Analytical curves for the simultaneous determination showed a linear response for both compounds. The acetaminophen presented a linear region in the concentration range 1.00 - 40.0 µmol L-1 with detection limit of 0.84 µmol L-1, and the caffeine presented a linear region, in the concentration range 4.00 - 200 µmol L-1 with detection limit of 1.6 µmol L-1. The proposed method was applied in the simultaneous determination of acetaminophen and caffeine in three pharmaceutical formulations, with results similar to those obtained using a HPLC method, at 95% confidence level (Student t-Test).